UOS / TON co-crystallized molecular sieve and its preparation method and application and UOS / TON co-crystallized molecular sieve composition and its application

Through the chemical composition of SiO2·1/x GeO2 and 3-diethylamino-1-propanol template agent, UOS/TON co-crystalline molecular sieve was prepared, which solved the problem of high synthesis cost and narrow range of UOS and TON molecular sieve, and achieved low Cost, efficient preparation of co-crystalline molecular sieve and extensive catalytic applications.

CN116002704BActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111235475.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-22
Publication Date
2025-01-03
Estimated Expiration
2041-10-22

AI Technical Summary

Technical Problem

The existing synthesis methods of UOS and TON molecular sieves have problems such as expensive template agents and narrow synthesis range, and the synthesis of TON molecular sieve requires high-speed stirring, which is prone to failure.

Method used

Using the chemical composition of SiO2·1/x GeO2, the UOS/TON co-crystallized molecular sieve is prepared by mixing silicon source, germanium source, fluorine source, organic template agent and water for crystallization reaction, and the weight percentage of UOS and TON molecular sieve can be Adjust to the range of 1% to 99%, and 3-diethylamino-1-propanol is used as the organic template agent to avoid high-speed stirring conditions.

Benefits of technology

The low-cost synthesis of UOS/TON co-crystalline molecular sieve is realized, with a simple organic template structure and a wide range of catalytic application prospects, avoiding the defects of single pore structure, and improving the catalytic activity and application flexibility of molecular sieve.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002704B_ABST
    Figure CN116002704B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of molecular sieves, and specifically to a UOS / TON co-crystallized molecular sieve, a preparation method and application thereof, and a UOS / TON co-crystallized molecular sieve composition and application thereof. The preparation method of the UOS / TON co-crystallized molecular sieve described in the present invention has the characteristics of a single and simple organic template structure, and the weight percentage of the UOS and TON molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%. The UOS / TON co-crystallized molecular sieve described in the present invention, after partially replacing the Si and Ge elements in the framework, can also introduce one or more of the other framework elements except Si and Ge into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of molecular sieves, and in particular to a UOS / TON co-crystallized molecular sieve and a preparation method and application thereof, and a UOS / TON co-crystallized molecular sieve composition and application thereof. Background Art

[0002] UOS molecular sieve is a mesoporous molecular sieve with three-dimensional cross channels, in which the 10-membered ring channel along the a-axis has an opening diameter of 0.36×0.63nm, and the opening diameters of the 8-membered ring channel along the b-axis and c-axis are 0.27×0.35nm and 0.30×0.30nm respectively. The unique channel system of UOS molecular sieve makes it have great application prospects in the fields of adsorption separation and catalytic conversion of organic matter. Researchers from the French Petroleum Research Institute first disclosed the structure and preparation method of UOS molecular sieve in French patent FR07 / 05.315. The template used in the synthesis is 3-ethyl-1-methylimidazolium ion (3-Ethyl-1-methyl-3H-imidazol-1-ium). The main problem of this synthesis method is that the template is expensive and the synthesis range of UOS molecular sieve is narrow.

[0003] TON molecular sieve is a medium-pore molecular sieve with a one-dimensional elliptical straight channel, a 10-membered ring opening, and a size of 0.46×0.57nm. Due to its mild acidic properties and spatial selectivity, ZSM-22 molecular sieve is used in the isomerization reaction of straight-chain alkanes, methanol to olefins, aromatic alkylation, hydrocracking, catalytic dewaxing, and alkane aromatization. Molecular sieves with TON structure include Theta-1 (US 5342596), ZSM-22 (US 4481177), NU-10 (US 4900528), ISI-1 (US 4483835), etc. The synthesis of TON molecular sieve usually needs to be carried out under high-speed stirring, otherwise the synthesis is likely to fail.

[0004] Co-crystallized molecular sieves refer to co-crystallization formed by two or more molecular sieves, or composite crystals with the structural characteristics of two or more molecular sieves. Since co-crystal molecular sieves have multiple structures and superposition functions, they avoid the defects of a single pore structure system, have great advantages in molecular adsorption and diffusion, and have broad application prospects in the field of oil refining catalysis. Summary of the invention

[0005] The purpose of the present invention is to provide a UOS / TON co-crystallized molecular sieve and its preparation method and application. The molecular sieve preparation method is simple, the synthesis cost is low, and the organic template structure is simple and single, and the weight percentage of UOS and TON molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%.

[0006] In order to achieve the above object, the present invention provides a UOS / TON co-crystallized molecular sieve on one hand, wherein the UOS / TON co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, and preferably the X-ray diffraction pattern of the UOS / TON co-crystallized molecular sieve includes characteristic peaks as shown in the following table:

[0007]

[0008] Among them, the molar ratio of SiO2 to GeO2 is 10≤x≤18.5, and the preferred molar ratio of SiO2 to GeO2 is 11≤x≤17.

[0009] The data in the above table represent the interplanar spacing of UOS / TON molecular sieve at 2θ(°) of 8.15±0.2. It is 10.85±0.50, and so on. The representation method of this table is well known to those skilled in the art, and the present invention will not explain them one by one here.

[0010] Preferably, in the UOS / TON co-crystallized molecular sieve, the weight percentage of the UOS molecular sieve is 1% to 99%, and the weight percentage of the TON molecular sieve is 1% to 99%.

[0011] Preferably, the weight percentage of the UOS molecular sieve is 5% to 95%, and the weight percentage of the TON molecular sieve is 5% to 95%.

[0012] Preferably, no more than 10 wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are substituted by at least one non-silicon tetravalent framework element Y.

[0013] Preferably, Y is selected from at least one of tin, titanium, zirconium and hafnium.

[0014] Preferably, 1-9 wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent framework element Y.

[0015] Preferably, no more than 20 wt% of the Ge atoms in the UOS / TON co-crystallized molecular sieve are substituted by at least one trivalent framework element X.

[0016] Preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.

[0017] Preferably, 2-16 wt% of the Ge atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one trivalent framework element X.

[0018] The second aspect of the present invention provides a method for preparing the UOS / TON co-crystallized molecular sieve of the present invention, the method comprising:

[0019] The step of mixing a silicon source, a germanium source, a fluorine source, an organic template agent N and water to perform a crystallization reaction to obtain a UOS / TON co-crystallized molecular sieve, wherein the organic template agent N is 3-diethylamino-1-propanol;

[0020] Among them, the silicon source calculated as SiO2 and the germanium source calculated as GeO2, SiO2:GeO2 is 1:0.054~0.1, preferably 1:0.059~0.091.

[0021] Preferably, the molar ratio of the organic template N, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is N:SiO2:GeO2:F:H2O=0.15~4:1:0.054~0.1:0.2~4:3~45.

[0022] Preferably, N:SiO2:GeO2:F:H2O=0.5~2:1:0.059~0.091:0.35~2.5:5~35.

[0023] Preferably, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.

[0024] Preferably, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.

[0025] Preferably, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.

[0026] Preferably, the method comprises: optionally mixing a non-silicon tetravalent skeleton element Y source and / or a trivalent skeleton element X source with the silicon source, germanium source, fluorine source, organic template N and water.

[0027] Preferably, the molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0-0.1, preferably 0.01-0.09.

[0028] Preferably, the molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.1, preferably 0.01-0.08.

[0029] Preferably, the conditions of the crystallization reaction include: a crystallization temperature of 100 to 200° C., preferably a crystallization temperature of 110 to 190° C.; and / or a crystallization time of 24 to 300 hours; preferably a crystallization time of 36 to 250 hours; and / or the crystallization is carried out under static conditions.

[0030] A third aspect of the present invention provides a UOS / TON co-crystallized molecular sieve composition, which comprises: the UOS / TON co-crystallized molecular sieve described in the present invention and a binder.

[0031] A fourth aspect of the present invention provides a use of the UOS / TON co-crystallized molecular sieve of the present invention or the UOS / TON co-crystallized molecular sieve composition of the present invention as an adsorbent or catalyst component.

[0032] The method for preparing the UOS / TON co-crystallized molecular sieve of the present invention has the characteristics of a simple and single organic template structure, and the weight percentage of the UOS and TON molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%. The UOS / TON co-crystallized molecular sieve of the present invention can also introduce one or more of the other framework elements except Si and Ge into the framework after partially replacing the Si and Ge elements in the framework, so as to produce different catalytic active centers and meet the needs of different catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the X-ray diffraction (XRD) pattern of the sample obtained in Example 1;

[0034] Figure 2 This is a scanning electron microscope (SEM) image of the sample obtained in Example 1;

[0035] Figure 3 is the X-ray diffraction (XRD) pattern of the sample obtained in Example 2;

[0036] Figure 4 This is a scanning electron microscope (SEM) image of the sample obtained in Example 2. DETAILED DESCRIPTION

[0037] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0038] According to one aspect of the present invention, the present invention provides a UOS / TON co-crystallized molecular sieve, wherein the UOS / TON co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, and preferably the X-ray diffraction pattern of the UOS / TON co-crystallized molecular sieve includes characteristic peaks as shown in the following table:

[0039]

[0040]

[0041] The molar ratio of SiO2 to GeO2 is 10≤x≤18.5, and preferably the molar ratio of SiO2 to GeO2 is 11≤x≤17. In the UOS / TON co-crystallized molecular sieve, the weight percentage of UOS and TON molecular sieves in the co-crystallized molecular sieve is adjustable within the range of 1% to 99%.

[0042] According to a preferred embodiment of the present invention, the UOS / TON co-crystallized molecular sieve comprises a UOS molecular sieve with a flake-like morphology and a TON molecular sieve with a needle-like morphology.

[0043] According to a preferred embodiment of the present invention, in the UOS / TON co-crystallized molecular sieve, the weight percentage of UOS molecular sieve is 1% to 99%, and the weight percentage of TON molecular sieve is 1% to 99%.

[0044] According to a preferred embodiment of the present invention, in the UOS / TON co-crystallized molecular sieve, the weight percentage of UOS molecular sieve is 5% to 95%, and the weight percentage of TON molecular sieve is 5% to 95%.

[0045] In the present invention, in the UOS / TON co-crystallized molecular sieve, the content of each molecular sieve is obtained by measuring the relative proportion of the sum of its characteristic diffraction peak areas to the sum of all diffraction peak areas.

[0046] According to the present invention, after partially replacing the Si and Ge elements in the framework of the UOS / TON co-crystallized molecular sieve, one or more other framework elements (such as non-silicon tetravalent framework elements and / or trivalent framework elements) other than Si and Ge can be introduced into the framework to produce different catalytic active centers to meet the needs of different catalytic reactions.

[0047] According to a preferred embodiment of the present invention, no more than 10wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y; preferably, the Y is selected from at least one of tin, titanium, zirconium and hafnium.

[0048] According to a preferred embodiment of the present invention, 1-9 wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y.

[0049] According to a preferred embodiment of the present invention, no more than 20wt% of the Ge atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one trivalent framework element X; preferably, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.

[0050] According to a preferred embodiment of the present invention, 2-16 wt% of Ge atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one trivalent framework element X.

[0051] The UOS / TON co-crystallized molecular sieves having the aforementioned characteristics can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a method for preparing the UOS / TON co-crystallized molecular sieve of the present invention, the method comprising:

[0052] The step of mixing a silicon source, a germanium source, a fluorine source, an organic template agent N and water to perform a crystallization reaction to obtain a UOS / TON co-crystallized molecular sieve, wherein the organic template agent N is 3-diethylamino-1-propanol;

[0053] The ratio of the silicon source in terms of SiO2 to the germanium source in terms of GeO2 is 1:0.054-0.1, preferably 1:0.059-0.091. The method for preparing the UOS / TON co-crystallized molecular sieve of the present invention has a simple organic template structure and a low synthesis cost.

[0054] According to a preferred embodiment of the present invention, the molar ratio of the organic template N, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is N:SiO2:GeO2:F:H2O=0.15~4:1:0.054~0.1:0.2~4:3~45; preferably N:SiO2:GeO2:F:H2O=0.5~2:1:0.059~0.091:0.35~2.5:5~35.

[0055] According to a preferred embodiment of the present invention, the silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane.

[0056] According to a preferred embodiment of the present invention, the germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium.

[0057] According to a preferred embodiment of the present invention, the fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride, preferably at least one of hydrofluoric acid and ammonium fluoride.

[0058] According to a preferred embodiment of the present invention, a non-silicon tetravalent skeleton element Y source and / or a trivalent skeleton element X source are optionally mixed with the silicon source, germanium source, fluorine source, organic template N and water; after partially replacing the Si and Ge elements in the skeleton, one or more of the other skeleton elements except Si and Ge can be introduced into the skeleton, for example, a non-silicon tetravalent skeleton element Y and / or a trivalent skeleton element X and other elements are introduced into the skeleton to generate different catalytic active centers to meet the needs of different catalytic reactions.

[0059] According to a preferred embodiment of the present invention, the molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0-0.1, preferably 0.01-0.09.

[0060] According to a preferred embodiment of the present invention, the Y is selected from at least one of tin, titanium, zirconium and hafnium.

[0061] According to the present invention, preferably, the tin source is selected from at least one of tin tetrachloride, stannous chloride, alkyl tin, alkoxy tin and organic tin esters; the titanium source is selected from at least one of tetraalkyl titanates (such as tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetra-n-butyl titanate), titanium tetrachloride, hexafluorotitanic acid, titanium sulfate and their hydrolyzates; the zirconium source and hafnium source are selected from conventional substances in the art, such as zirconium nitrate, zirconium oxychloride, hafnium sulfate, etc.

[0062] According to a preferred embodiment of the present invention, the molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.1, preferably 0.01-0.08.

[0063] According to a preferred embodiment of the present invention, X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.

[0064] According to the present invention, preferably, the aluminum source is selected from at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, aluminum chloride, pseudo-boehmite, aluminum oxide, aluminum hydroxide, silica-aluminum zeolite molecular sieve, aluminum carbonate, elemental aluminum, aluminum isopropoxide and aluminum acetate; the boron source is selected from at least one of boric acid, sodium tetraborate, amorphous boron oxide, potassium borate, sodium metaborate, ammonium tetraborate and organic boron esters; the iron source is selected from at least one of ferric sulfate, ferric nitrate, iron halide (such as ferric chloride), ferrocene and ferric citrate; the gallium source, indium source and chromium source are selected from conventional substances in the art, such as gallium oxide, gallium nitrate, indium oxide, indium nitrate, chromium chloride, chromium nitrate and the like.

[0065] According to a preferred embodiment of the present invention, the conditions of the crystallization reaction include: a crystallization temperature of 100 to 200°C, preferably a crystallization temperature of 110 to 190°C, and more preferably a crystallization temperature of 150 to 180°C.

[0066] According to a preferred embodiment of the present invention, the conditions of the crystallization reaction include: a crystallization time of 24 to 300 hours; preferably a crystallization time of 36 to 250 hours, and more preferably a crystallization time of 96 to 216 hours.

[0067] According to a preferred embodiment of the present invention, the crystallization reaction conditions include crystallization at 100-200° C. for 24-300 hours; preferably crystallization at 110-190° C. for 36-250 hours.

[0068] According to a preferred embodiment of the present invention, the crystallization is carried out under static and / or dynamic conditions. The preparation method of the UOS / TON co-crystallized molecular sieve provided by the present invention has the advantages of simple organic template structure and high product purity can be obtained without static crystallization under high-speed stirring conditions. In the present invention, the results of static or dynamic crystallization remain basically consistent, and the embodiments of the present invention do not specifically illustrate static or dynamic.

[0069] According to the present invention, preferably, after the crystallization reaction is completed, conventional post-treatment is performed, such as filtering, washing, and drying to obtain the molecular sieve; and optionally, a step of calcining the obtained molecular sieve.

[0070] A third aspect of the present invention provides a UOS / TON co-crystallized molecular sieve composition, which comprises: the UOS / TON co-crystallized molecular sieve described in the present invention and a binder.

[0071] The present invention has no particular limitation on the binder, and any binder in the art can be used as the binder described in the present invention.

[0072] A fourth aspect of the present invention provides a use of the UOS / TON co-crystallized molecular sieve of the present invention or the UOS / TON co-crystallized molecular sieve composition of the present invention as an adsorbent or catalyst component.

[0073] In the context of this specification, the structure of the molecular sieve is determined by an X-ray diffraction spectrum (XRD), which is measured by an X-ray powder diffractometer using a Cu-Kα ray source with a Kα1 wavelength of λ=1.5405980 angstroms. Nickel filter.

[0074] In the present invention, an X'Pert PRO X-ray powder diffraction (XRD) instrument of PANalytical Company of the Netherlands is used, with an operating voltage of 40 kV, a current of 40 mA, and a scanning range of 5 to 40°. The product morphology is photographed using an S-4800 field emission scanning electron microscope (Fe-SEM) of HITACHI Company of Japan.

[0075] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solutions (such as methods or systems) thus formed are part of the original disclosure of this specification and also fall within the scope of protection of the present invention.

[0076] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the common understanding of those skilled in the art.

[0077] Example 1

[0078] Mix 4.94g 3-diethylamino-1-propanol (DEAP) and 5.6g water evenly, add 0.246g germanium oxide, and slowly add 5.65g Ludox silica sol (SiO2 40wt%) under stirring after dissolution, continue stirring at room temperature for 3h, and finally add 1.88g hydrofluoric acid (40wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with polytetrafluoroethylene lining, and place it in a 165℃ oven for crystallization for 144 hours. After the reaction, the solid is filtered, washed with distilled water, and dried at 100℃ to obtain the original powder solid, which is placed in a muffle furnace and calcined at 550℃ for 5 hours to obtain the final product. The XRD spectrum is as follows Figure 1 As shown by Figure 1 It can be seen that the product is a UOS / TON co-crystallized molecular sieve, in which the UOS molecular sieve content is 25%. The spectrum data is shown in Table 1, and the SEM photo is shown in Figure 2 As shown by Figure 2 It can be seen that the product contains both UOS molecular sieve flake crystals and TON molecular sieve needle crystals. The raw material composition for synthesizing the molecular sieve is shown in Table 5.

[0079] Table 1

[0080]

[0081]

[0082] Example 2

[0083] Mix 4.36g 3-diethylamino-1-propanol (DEAP) and 2.3g water evenly, add 0.322g germanium oxide, and slowly add 5.54g Ludox silica sol (SiO2 40wt%) under stirring after dissolving, continue stirring at room temperature for 3h, and finally add 1.66g hydrofluoric acid (40wt%), continue stirring for 1 hour, then put the above mixture into a crystallization kettle with a polytetrafluoroethylene liner, and place it in a 170℃ oven for crystallization for 120 hours. The solid after the reaction is filtered, washed, dried, and calcined to obtain the final product. The XRD spectrum is as follows Figure 3 As shown by Figure 3 It can be seen that the product is a UOS / TON co-crystallized molecular sieve, in which the UOS molecular sieve content is 70%. The spectrum data is shown in Table 2, and the SEM photo is shown in Figure 4 As shown by Figure 4 It can be seen that the product contains both UOS molecular sieve flake crystals and TON molecular sieve needle crystals. The raw material composition for synthesizing the molecular sieve is shown in Table 5.

[0084] Table 2

[0085]

[0086] Example 3

[0087] 5.98g 3-diethylamino-1-propanol (DEAP) was mixed with 1.8g water, 0.364g germanium oxide was added, and 4g Ludox silica sol (SiO2 40wt%) and 0.62g white carbon black (SiO2 95wt%) were slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2.28g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 175°C oven for crystallization for 132 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 85%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0088] Example 4

[0089] 7.45g 3-diethylamino-1-propanol (DEAP) was mixed with 3.2g water, 0.22g germanium oxide was added, and 5.68g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 1.6g hydrofluoric acid (40wt%) and 1.53g ammonium fluoride aqueous solution (37wt%) were added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 150°C oven for crystallization for 192 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 15%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0090] Example 5

[0091] 7.39g 3-diethylamino-1-propanol (DEAP) was mixed with 8.7g water, 0.262g germanium oxide was added, and after dissolving, 3g Ludox silica sol (SiO2 40wt%) and 1.11g white carbon black (SiO2 95wt%) were slowly added under stirring, and stirring was continued for 3h at room temperature, and finally 2.5g hydrofluoric acid (40wt%) and 2.5g ammonium fluoride aqueous solution (37wt%) were added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 170°C oven for crystallization for 168 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 45%. The XRD spectrum data are shown in Table 3. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0092] Table 3

[0093]

[0094] Example 6

[0095] 3.67g 3-diethylamino-1-propanol (DEAP) was mixed with 12.8g water, 0.289g germanium oxide was added, and after dissolving, 0.84g Ludox silica sol (SiO2 40wt%) and 2g white carbon black (SiO2 95wt%) were slowly added under stirring, and stirring was continued for 3h at room temperature, and finally 5.6g ammonium fluoride aqueous solution (37wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 180°C oven for crystallization for 96 hours. After the reaction, the solid was filtered, washed, dried, and roasted to obtain the final UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 55%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0096] Example 7

[0097] 5.9g 3-diethylamino-1-propanol (DEAP) was mixed with 5.4g water, 0.279g germanium oxide and 0.142g aluminum sulfate 18 hydrate were added, and 5.6g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2.24g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 165°C oven for crystallization for 180 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final Al-UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 50%. The XRD spectrum data are shown in Table 4. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0098] Table 4

[0099]

[0100]

[0101] Example 8

[0102] 5.9g 3-diethylamino-1-propanol (DEAP) was mixed with 5.4g water, 0.279g germanium oxide, 0.017g boric acid and 0.153g titanium sulfate were added, and 5.6g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2.24g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 155°C oven for crystallization for 216 hours. After the reaction, the solid was filtered, washed, dried and calcined to obtain the final B-Ti-UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 40%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0103] Example 9

[0104] 5.9g 3-diethylamino-1-propanol (DEAP) was mixed with 5.4g water, 0.279g germanium oxide and 0.17g aluminum sulfate 18 hydrate were added, and 5.6g Ludox silica sol (SiO2 40wt%) was slowly added under stirring after dissolution, and stirring was continued for 3h at room temperature, and finally 2.24g hydrofluoric acid (40wt%) was added, and stirring was continued for 1 hour, and the above mixture was loaded into a crystallization kettle with a polytetrafluoroethylene liner, and placed in a 165°C oven for crystallization for 180 hours. After the reaction, the solid was filtered, washed, dried, and calcined to obtain the final Al-UOS / TON co-crystallized molecular sieve product, wherein the UOS molecular sieve content was 48%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0105] Example 10

[0106] 5.9g 3-diethylamino-1-propanol (DEAP) was mixed with 5.4g water, and 0.279g germanium oxide, 0.03g boric acid and 0.7g titanium sulfate were added. After dissolution, 5.6g Ludox silica sol (SiO2 40wt%) was slowly added under stirring, and stirring was continued for 3h at room temperature. Finally, 2.24g hydrofluoric acid (40wt%) was added. After stirring for 1 hour, the above mixture was placed in a crystallization kettle with a polytetrafluoroethylene liner and placed in a 155°C oven for crystallization for 216 hours. After the reaction, the solid was filtered, washed, dried and calcined to obtain the final B, Ti-UOS / TON co-crystallized molecular sieve product, in which the UOS molecular sieve content was 20%. The composition of the raw materials for synthesizing the molecular sieve is shown in Table 5.

[0107] Table 5 Example Molecular Sieve Raw Material Molecular Ratio Composition

[0108] project <![CDATA[SiO2 / GeO2]]> <![CDATA[Q / SiO2]]> F / Si <![CDATA[H2O / Si]]> <![CDATA[YO2 / SiO2]]> <![CDATA[X2O3 / GeO2]]> Example 1 16 1 1 15 0 0 Example 2 12 0.9 0.9 10 0 0 Example 3 10.5 1.25 1.25 8.5 0 0 Example 4 18 1.5 1.25 12.5 0 0 Example 5 15 1.5 2 20 0 0 Example 6 13.5 0.75 1.5 25 0 0 Example 7 14 1.2 1.2 15 0 0.08 Example 8 14 1.2 1.2 15 0.02 0.05 Example 9 14 1.2 1.2 15 0 0.096 Example 10 14 1.2 1.2 15 0.092 0.091

[0109] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A UOS / TON co-crystallized molecular sieve, characterized in that: The UOS / TON co-crystallized molecular sieve has a schematic chemical composition as shown in the formula: SiO2·1 / x GeO2, wherein the molar ratio of SiO2 to GeO2 is 10≤x≤18.5; The X-ray diffraction spectrum of the UOS / TON co-crystallized molecular sieve includes characteristic peaks as shown in the following table:

2. The UOS / TON co-crystallized molecular sieve according to claim 1, wherein The molar ratio of SiO2 to GeO2 is 11≤x≤17.

3. The UOS / TON co-crystallized molecular sieve according to claim 1 or 2, wherein: The UOS / TON co-crystallized molecular sieve comprises a UOS molecular sieve with a flake morphology and a TON molecular sieve with a needle morphology; and / or In the UOS / TON co-crystallized molecular sieve, the weight percentage of the UOS molecular sieve is 1% to 99%, and the weight percentage of the TON molecular sieve is 1% to 99%.

4. The UOS / TON co-crystallized molecular sieve according to claim 3, wherein: In the UOS / TON co-crystallized molecular sieve, the weight percentage of the UOS molecular sieve is 5% to 95%, and the weight percentage of the TON molecular sieve is 5% to 95%.

5. The UOS / TON co-crystallized molecular sieve according to claim 1 or 2, wherein: No more than 10 wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent framework element Y; and / or No more than 20 wt % of the Ge atoms in the UOS / TON co-crystallized molecular sieve are substituted by at least one trivalent framework element X.

6. The UOS / TON co-crystallized molecular sieve according to claim 5, wherein: The Y is selected from at least one of tin, titanium, zirconium and hafnium.

7. The UOS / TON co-crystallized molecular sieve according to claim 5, wherein: 1-9wt% of Si atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one non-silicon tetravalent skeleton element Y.

8. The UOS / TON co-crystallized molecular sieve according to claim 5, wherein: The X is selected from at least one of aluminum, boron, iron, gallium, indium and chromium.

9. The UOS / TON co-crystallized molecular sieve according to claim 5, wherein: 2-16 wt% of the Ge atoms in the UOS / TON co-crystallized molecular sieve are replaced by at least one trivalent framework element X.

10. A method for preparing the UOS / TON cocrystallized molecular sieve according to any one of claims 1 to 9, characterized in that: The method includes: The step of mixing a silicon source, a germanium source, a fluorine source, an organic template agent N and water to perform a crystallization reaction to obtain a UOS / TON co-crystallized molecular sieve, wherein the organic template agent N is 3-diethylamino-1-propanol; Among them, the silicon source calculated as SiO2 and the germanium source calculated as GeO2, the molar ratio of SiO2: GeO2 is 1: 0.054~0.

1.

11. The method for preparing the UOS / TON co-crystallized molecular sieve according to claim 10, wherein: The silicon source calculated as SiO2 and the germanium source calculated as GeO2 have a molar ratio of SiO2:GeO2 of 1:0.059~0.

091.

12. The preparation method according to claim 10, wherein: The molar ratio of the organic template N, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is N: SiO2: GeO2: F: H2O = 0.15~4: 1: 0.054~0.1: 0.2~4: 3~45.

13. The preparation method according to claim 12, wherein: The molar ratio of the organic template N, the silicon source calculated as SiO2, the germanium source calculated as GeO2, the fluorine source calculated as F and water is N: SiO2: GeO2: F: H2O = 0.5~2: 1: 0.059~0.091: 0.35~2.5: 5~35.

14. The preparation method according to any one of claims 10 to 13, wherein: The silicon source is at least one selected from the group consisting of water glass, silica sol, solid silica gel, fumed silica, amorphous silica, diatomaceous earth, zeolite molecular sieve and tetraalkoxysilane; and / or The germanium source is selected from at least one of germanium oxide, germanium nitrate and tetraalkoxygermanium; and / or The fluorine source is selected from at least one of hydrofluoric acid, ammonium fluoride, sodium fluoride and potassium fluoride.

15. The preparation method according to claim 14, wherein: The fluorine source is selected from at least one of hydrofluoric acid and ammonium fluoride.

16. The preparation method according to any one of claims 10 to 13, wherein: The method includes: The non-silicon tetravalent skeleton element Y source and / or the trivalent skeleton element X source are mixed with the silicon source, the germanium source, the fluorine source, the organic template N and the water.

17. The preparation method according to claim 16, wherein: The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0~0.

1.

18. The preparation method according to claim 17, wherein: The molar ratio of the non-silicon tetravalent skeleton element Y source calculated as the corresponding oxide YO2 to the silicon source calculated as SiO2 is YO2 / SiO2=0.01~0.

09.

19. The preparation method according to claim 16, wherein: The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0-0.

1.

20. The preparation method according to claim 19, wherein: The molar ratio of the trivalent skeleton element X source calculated as the corresponding oxide X2O3 to the germanium source calculated as GeO2 is X2O3 / GeO2=0.01-0.

08.

21. The preparation method according to any one of claims 10 to 13, wherein: The conditions of the crystallization reaction include: The crystallization temperature is 100-200 ºC; and / or The crystallization time is 24 to 300 hours; and / or The crystallization is performed under static and / or dynamic conditions.

22. The preparation method according to claim 21, wherein The crystallization temperature is 110~190 ºC.

23. The preparation method according to claim 21, wherein The crystallization temperature is 150~180 ºC.

24. The preparation method according to claim 21, wherein The crystallization time is 36~250 hours.

25. The preparation method according to claim 21, wherein The crystallization time is 96~216 hours.

26. A UOS / TON co-crystallized molecular sieve composition, characterized in that: The composition comprises: the UOS / TON co-crystallized molecular sieve described in any one of claims 1 to 9 and a binder.

27. Use of the UOS / TON co-crystallized molecular sieve according to any one of claims 1 to 9 or the UOS / TON co-crystallized molecular sieve composition according to claim 26 as an adsorbent or catalyst component.